MODEL HILYAQIS DALAM MEMBANGUN SEKOLAH BERKUALITAS MELALUI PEMBELAJARAN MODERASI BERAGAMA DI MTS WALI SONGO SITUBONDO - Syamsul Arifin; Halid, Ahmad; Hasan bin Jali (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2024)
Quality schools are not only measured from academic aspects, but also from the development of students' character and morals based on religious values. This article examines the role of the Hilyaqis learning model in building a quality school at MTs Wali Songo, with an emphasis on the application of religious moderation through the verses of the Qur'an, Hadith, and stories of scholars. Hilyaqis learning carries an approach that combines Islamic teachings with everyday life, with the aim of producing a generation that not only excels in academics, but also has a moderate and tolerant character. Through the integration of Islamic teachings in each sub-chapter of learning, students are given an understanding of the importance of tolerance, simplicity, and peace in religion, and are taught to avoid extremism. The stories of scholars who uphold the values ​​of moderation become role models that inspire students to apply these values ​​in their lives. This study proves that the application of the Hilyaqis learning model at MTs Wali Songo plays a crucial role in strengthening religious moderation, shaping students' Islamic character, and creating an inclusive and harmonious educational environment. Therefore, this approach not only improves the quality of education, but also encourages the creation of quality schools both academically and morally.